Electrochemical sensor for bisphenol A detection in the environment to prevent human health problems - Nisa Ulfiatun; Putri Salsa Saloma; Heryanto Rudi; Putra Budi Riza; Wahyuni Wulan Tri (BIO Web of Conferences)
Bisphenol A (BPA) is increasingly released into water, soil, and air, becoming an environmental pollutant. Since BPA is persistent in the environment, it remains there for a considerable amount of time and allows bioaccumulation, potentially affecting ecosystems and human health. For that reason, the detection of BPA in the environment is essential. In this study, we develop an electrochemical sensor for simple and rapid detection of BPA in a water environment. The sensor was developed using a glassy carbon electrode (GCE) modified with conductive materials. The detection of BPA was carried out based on the oxidation of BPA on modified GCE using a differential pulse voltammetry technique. The developed sensor performs acceptable analytical performance with a detection limit of 0.5 μM and sensitivity of 0.22 μA μM-1. The developed sensor also has the potency for BPA detection in water samples.